Stigma and illness uncertainty: adding to the burden of sickle cell disease. Issue 2 (7th February 2018) - Blake, Alphanso; Asnani, Vikram; Leger, Robin R.; Harris, June; Odesina, Victoria; Hemmings, Daileann L.; Morris, Denise A.; Knight-Madden, Jennifer; Wagner, Linda; Asnani, Monika Rani
ABSTRACT: Background: Persons with sickle cell disease (SCD) experience multiple medical and physical complications; the disease also has numerous effects on their social and emotional well-being. We hypothesized that adults with SCD in Jamaica experience moderate levels of stigma and illness uncertainty and that these experiences may be associated with socio-demographic factors, such as gender, educational status and economic status. Methods: We surveyed 101 adults with SCD (54.5% female; mean age 31.6 ± 10.4 years; 72.2% homozygous SCD) using the Stigma in Sickle Cell Disease Scale (Adult), Mishel Uncertainty in Illness Scale (Adult) and a Socio-Demographic questionnaire. Results: The mean stigma score was 33.6 ± 21.6 (range: 2–91) with no significant difference between males and females (32.3 ± 21.3 vs. 34.7 ± 21.9; p -value = 0.58). Illness uncertainty was greater in females than in males, though not statistically significant, (88.7 ± 13.5 vs. 82.6 ± 19.2; p -value: 0.07). Stigma and uncertainty had a significant positive correlation (r: 0.31; p -value: 0.01). In an age and sex controlled model, stigma scores were lower with higher numbers of household items (coef: −2.26; p -value: 0.001) and higher in those living in greater crowding (coef: 7.89; p -value: 0.002). Illness uncertainty was higher in females (coef: 6.94; p -value: 0.02) and lower with tertiary as compared with primary education (coef: −16.68; p -value: 0.03). Conclusion: The study highlights socioeconomic factors to be significant to the stigma and illness uncertainty experiences in SCD. Efforts by healthcare workers to reduce patient illness uncertainty may have additional impact, reducing their stigma.